The power of individual-level drivers of inventive performance - Thomas Zwick; Katharina Frosch; Karin Hoisl; Dietmar Harhoff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Based on an established theoretical framework of the drivers of inventive performance, the so-called KSAO (Knowledge, Skills, Abilities, and Other) factors, this paper seeks to explain empirically the performance of inventors throughout their careers. We combine survey information spanning the inventors' entire careers and psychometric test evidence, with patent history data for more than 1,000 inventors. We also control for variables that have traditionally been included in estimations of inventive performance such as inventor age and a broad list of applicant institution-, technology-, patent-, and period-related information. We show that educational level, skills acquired during the career, personality traits, career motivations, cognitive abilities, and cognitive problem-solving style are significantly related to inventive performance.
urn:nbn:de:bsz:180-madoc-401637
Keywords: J24; M54; O31; O32; 330; inventive performance; individual drivers; patent history; survey